Biohistory - Penman, Jim (Cambridge Scholars Publishing, 2015)
Biohistory is a revolutionary new theory that explores the biological and behavioural underpinnings of social change, including the rise and fall of civilisations. Informed by significant research into the physiological basis of behaviour conducted by author Dr Jim Penman and a team of scientists at RMIT University and the Florey Institute in Melbourne, Australia, Biohistory examines how a complex interplay between culture and biology has shaped civilisations from the Roman Empire to the modern West. Penman proposes that historical changes are driven by changes in the prevailing temperament of populations, based on physiological mechanisms that adapt animal behaviour to changing food conditions. It details the history of human society by mapping the effects of these epigenetic changes on cultures, and on historical tipping points including wars and revolutions. It shows how laboratory studies can be used to explain broad social and economic changes, including the fortunes of entire civilizations. The author's shocking conclusion is that the West is in terminal and inevitable decline, and that its only hope may lie with the biological sciences. Drawing on the disciplines of history, biology, anthropology and economics, Biohistory is the first theory of society that can be tested with some rigour in the laboratory. It explains how environment, cultural values and childrearing patterns determine whether societies prosper or collapse, and how social change can be both predicted-and potentially modified-through biochemistry.